2003
DOI: 10.1152/japplphysiol.00079.2003
|View full text |Cite
|
Sign up to set email alerts
|

Selected Contribution: Bone adaptation with aging and long-term caloric restriction in Fischer 344 × Brown-Norway F1-hybrid rats

Abstract: Rodents are commonly used as models for human aging because of their relatively short life span, the ease of obtaining age-specific tissue samples, and lower cost. However, age-associated disease may confound inbred animal studies. For example, numerous physiologically significant lesions, such as chronic nephropathy, are more common in aged Fischer 344 (F344) rats than in other strains (Bronson RT, Genetic Effects of Aging, 1990). Conversely, F344 x Brown-Norway F1-hybrid (F344BN) rats, developed by the Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 36 publications
8
36
3
1
Order By: Relevance
“…Caloric restriction was shown to be associated with bone loss in middle-aged humans (Villareal et al 2006) and late-middle-aged rodents (LaMothe et al 2003); however, no changes in BMD were observed in this study, maybe due to the differences in age.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Caloric restriction was shown to be associated with bone loss in middle-aged humans (Villareal et al 2006) and late-middle-aged rodents (LaMothe et al 2003); however, no changes in BMD were observed in this study, maybe due to the differences in age.…”
Section: Discussioncontrasting
confidence: 77%
“…In recent years, the effect of RES on bone quality was assessed in several studies using micro-CT scanning and mechanical testing. However, most of these studies were carried out on adult animals and used diverse protocols, including different species (mostly mice and rats) of various ages, sex and strains, different extent, and duration of the restriction (from 4 weeks to 4 months) with matched or non-matched intake of micronutrients (Talbott et al 2001, LaMothe et al 2003, Lambert et al 2005. These variations make it quite difficult to make valid comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Significant signs of sarcopenia in the Fischer 344 ϫ Brown Norway rats do not fully manifest until 33months of age (Lushaj et al, 2008). Although these rats reach skeletal maturity at ~6months, they increase in body mass in the form of adipose and connective tissues until ~30months of age, similar to the human trajectory (LaMothe et al, 2003;Lushaj et al, 2008;Turturro et al, 1999). Individuals were housed separately in standard laboratory rat cages in a temperature-regulated room (22-23°C) on a 12h:12h light:dark cycle and were provided with food and water ad libitum.…”
Section: Materials and Methods Animalsmentioning
confidence: 96%
“…Tibial geometry permits more stable and repeatable placement of the diaphyseal shaft on the loading span than the femoral diaphysis, which is more circular in cross section (23) . On the day of mechanical testing, tibiae were thawed in 228C PBS for at least 1 h. Tibial length was measured (^0·01 mm) using digital callipers (Model 14-648-17, Fisher Scientific, Ottawa, ON, Canada).…”
Section: Mechanical Testing: Three-point Bendingmentioning
confidence: 99%